Order and disorder under the Ancien Régime - Merrick, Jeffrey (Cambridge Scholars Publ., 2007)
This collection of revised and previously unpublished articles explores aspects of the history of monarchy, family, suicide, and sodomy in early modern, especially eighteenth-century France. The durable but flexible traditions of the Ancien Régime not only sanctified but also limited the prerogatives of sovereigns over subjects and husbands/fathers/masters over wives, children, and servants. Private and public weakness and excess in those who ruled the kingdom and the household undermined their masculinity and legitimacy. Merrick analyzes expositions of and contestations about the origins, extent, and use and abuse of gendered royal and domestic authority in a wide variety of sources, including descriptions of beehives, pamphlets published during the Fronde, statues of Louis XV, police reports about disturbed subjects, parlementary remonstrances, Jansenist polemics, essays submitted to the Academy of Berlin, the memoirs of the marquis de Bombelles, and complaints of wives against husbands and marital separation cases in Paris. In principle, kings and husbands/fathers/masters preserved order in the kingdom and the household by controlling themselves as well as their subordinates. In practice, they sometimes provoked disorder and failed in many ways to prevent and punish disorder. Merrick's articles on suicide and sodomy not only revisit some celebrated incidents (the deaths of the dragoons Bourdeaux and Humain, who shot themselves on 25 December 1773) and notorious characters (the pederast marquis de Villette and tribade mademoiselle de Raucourt) but also document patterns in the lives and deaths of ordinary men and women. Based, like the articles on marital disputes, on extensive archival research, they investigate changes in jurisprudence and mentalities during the eighteenth century. As a whole, this volume challenges simplistic assumptions about absolutism, Enlightenment, and Revolution.